Winds of change : an analysis of the duties of the Irish State relevant to the development and sale of electricity from onshore wind - Barrett, Eva (Trinity College (Dublin, Ireland). School of Law, 2015)
This thesis seeks to analyse 'the duties of the Irish State which are relevant to the development and sale of electricity from onshore wind.' While it might be more traditional to have one core research question, the subject-matter of the thesis lends itself more naturally to the following three questions: (i) What legal duties placed on the Irish government are relevant to the generation and sale of electricity from onshore wind? (ii) Has Ireland fulfilled these duties (and if not, are solutions available)? (iii) What consequences follow any failures, which have been discovered? In a nutshell, it is concluded that while Ireland's commitment to developing renewable energy is highly commendable, its underlying strategy has unintentionally caused multiple breaches of EU law and is unlikely to deliver the levels of renewable energy necessary to fulfil Ireland's overarching legal obligations. This is believed to be due to the failure of the Irish government to conduct a full and careful analysis of the surrounding legal environment prior to finalising its 10 year onshore wind development strategy, an oversight which has left Ireland exposed to the risk of the public and private enforcement actions, discussed in the thesis.
Keywords: Law, Ph.D.; Ph.D. Trinity College Dublin.